2020
DOI: 10.1111/ijac.13617
|View full text |Cite
|
Sign up to set email alerts
|

A green composite material of calcium phosphate cement matrix with additions of car tire waste particles

Abstract: The car tire waste have a tremendous adverse environmental impact in nature due to the large volumes generated worldwide, which requires multiple solutions that decrease as much as possible the tires disposed in landfills. Therefore, this research proposes to use part of the unused tire waste in a construction material, phosphate cement with ground rubber waste particles. For that, up to 12wt% of tire waste has been incorporated to cement. The samples characterization was conducted with scanning electron micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…Several studies indicate that dicalcium phosphate dehydrate (DCPD)-commonly known as brushite, with the chemical formula CaHPO 4 •2H 2 O-is one of the most widely used CaPs [8,11]. This mineral acts as a precursor of hydroxyapatite (HA), bone cement, and bioceramics.…”
Section: Of 12mentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies indicate that dicalcium phosphate dehydrate (DCPD)-commonly known as brushite, with the chemical formula CaHPO 4 •2H 2 O-is one of the most widely used CaPs [8,11]. This mineral acts as a precursor of hydroxyapatite (HA), bone cement, and bioceramics.…”
Section: Of 12mentioning
confidence: 99%
“…Moreover, two sharp peaks reflect the mass loss as a result of heating from 80 to 220 • C. Brushite is characterized by two water molecules in its lattice and adsorbed water molecules on its surface [42,43]. Available evidence indicates that some of the chemically-bound water is released as brushite transforms to monetite (CaHPO 4 ) at ≈220 • C [44] and further to calcium pyrophosphate (Ca 2 P 2 O 7 ) as the temperature increases to ≈440 • C [8]. According to our results, when pure brushite (BNi0) is heated to 750 • C, approximately 21 wt % of its mass is lost [10], which is comparable to the theoretical mass loss of 20.93 wt % [45].…”
Section: Thermogravimetric Analysis (Tga)mentioning
confidence: 99%
See 1 more Smart Citation
“…Other investigations include the use of micromechanical models in acrylic composites with particle fillers, 25 unidirectional reinforced with fibers, 26,27 linear elastic fiber, 28,29 piezoelectric, 30,31 multiphase, 32 among others. There are very few studies 33 regarding composite materials involving calcium phosphate cement with rubber waste particles, although nothing related to adhesion between these two materials, or to the cement in combination with a rubber based layer, in a sandwich‐structured composite configuration. For this reason, the study of the interface in a calcium phosphate cement matrix reinforced with rubber residues is the central point of this research, which is identified as very important since the properties of the composite material are significantly affected by its interface 34,35 .…”
Section: Introductionmentioning
confidence: 99%
“…e resistivity of cement material was tested by the direct current four-terminal electrode method, and the influence of the water content of carbon fiber cement material [26] on its resistivity was studied [27]. A simulation test device was designed and the scanning electron microscope test method [28,29] was adopted to prove that grouting can not only improve the physical and mechanical properties of rocks, but also cause chemical changes in rock components and generate petrolike minerals in the interface region, thus improving the cementation strength of the rock-slurry interface [30][31][32][33]. As observed, the above researches mainly considered the ratio of a selected aggregate of materials, which are mostly limited to the testing of the bearing capacity of cement slurry and do not significantly consider the cohesiveness and the actual load-bearing characteristics after reinforcement and surface spalling.…”
Section: Introductionmentioning
confidence: 99%